2016
DOI: 10.3847/0004-637x/826/1/48
|View full text |Cite
|
Sign up to set email alerts
|

Suprathermal Electrons at Saturn's Bow Shock

Abstract: The leading explanation for the origin of galactic cosmic rays is particle acceleration at the shocks surrounding young supernova remnants (SNRs), although crucial aspects of the acceleration process are unclear. The similar collisionless plasma shocks frequently encountered by spacecraft in the solar wind are generally far weaker (lower Mach number) than these SNR shocks. However, the Cassini spacecraft has shown that the shock standing in the solar wind sunward of Saturn (Saturnʼs bow shock) can occasionally… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…This study follows directly from the results presented by Masters et al (2016), who searched for evidence of electron acceleration at these Cassini shock crossings. These authors identified three crossings with particularly strong energetic electron signatures, which cannot be explained as a result of leakage of energetic electrons from within Saturn's magnetic field environment.…”
Section: Observationsmentioning
confidence: 73%
See 2 more Smart Citations
“…This study follows directly from the results presented by Masters et al (2016), who searched for evidence of electron acceleration at these Cassini shock crossings. These authors identified three crossings with particularly strong energetic electron signatures, which cannot be explained as a result of leakage of energetic electrons from within Saturn's magnetic field environment.…”
Section: Observationsmentioning
confidence: 73%
“…These crossings took place predominantly on the dayside of the shock surface, and under a range of upstream conditions. Data taken during shock crossings by Cassini have been surveyed by Sulaiman et al (2016) and Masters et al (2016), who discussed the extent of information about each crossing that can be extracted from Cassini data sets. These studies provide an estimated Alfvén Mach number of each crossing, as well as a separation of the crossings by shock geometry (quasiparallel/quasi-perpendicular).…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations first made at Earth and more recently extended to Saturn have shown a relationship between M w and electron acceleration [ Oka et al ., ; Masters et al ., ]. The spectral index of the electron energy spectrum was found to be controlled by MA / M w — i.e., electron acceleration was prominent at supercritical shocks.…”
Section: Resultsmentioning
confidence: 99%
“…There are two critical Mach numbers associated with quasi-perpendicular collisionless shocks. The first represents the upper limit in solar wind flow speed at which the shock has the capacity to sufficiently dissipate the incident flow by anomalous resistivity and/or wave dispersion [Marshall, 1955;Kennel et al, 1985]. Above this, the shock adopts an alternative mechanism, namely, ion reflection, to convert the excess ram energy into thermal energy [Paschmann et al, 1981;Treumann, 2009].…”
Section: Introductionmentioning
confidence: 99%